Drivers and Outcomes of Perceived Authenticity of Online Reviews - Alkhamisi, Lujain (Curtin University, 2023)
Drawing on the leakage theory and adopting a mixed methods research approach, this thesis explores perceived authenticity of online reviews in terms of defining the concept, identifying its essential elements, key drivers, and consequences. The findings revealed that verbal and non-verbal factors drive perceived authenticity, which eventually influences review persuasiveness and users’ behavioural intention. The findings extend the leakage theory and offer a better understanding of human detection of authentic (vs. fake) online reviews.